Sustainable geopolymer using lithium concentrate residues. (20th December 2019) - Karrech, A.; Dong, M.; Elchalakani, M.; Shahin, M.A.
Highlights: Lithium aluminosilicate residue as a new geopolymer precursor. High strength geopolymer achieved using lithium aluminosilicate residue. Lithium aluminosilicate residue has a retardation effect on the curing of geopolymer. Lithium aluminosilicate residue reduces the extent of micro-cracking. Abstract: Australia is a key player in the global supply of lithium products given its large resources of spodumene. This mineral occurs in pegmatite rocks and can be processed to extract lithium salts used to make valuable products such as lithium ion batteries, ceramics, lubricants along with specific by-products such as lithium aluminosilicate residue (LASR). This paper investigates, for the first time, the use of LASR as a geopolymer precursor. A total of ten mixes have been synthesised, comparing the performance of LASR, fly ash, ground granulated blust-furnace slag (GGBS), kaolin and metakaolin. Ranges of mechanical and chemical tests have been carried out to examine the hardening of the mixes. Our experimental results reveal that LASR has a good thermal stability up to 1000 °C. While it has a low reactivity in alkaline solutions, its presence significantly improves the efficiency of other binder materials. LASR particles bridge the gaps between the larger sand grains, resulting in reduced micro-cracking. Based on the hardening trends, pH measurements and XRD analysis, we noticed that LASR could effectively retard the setting of geopolymer mixtures. A high 28-day compressive strength of 84.8 MPa has been obtained in the mix with 50% LASR and 50% GGBS; this mix produces three times higher strength than conventional concrete. With the delayed reactions and lower extent of micro-cracks, our hardening tests suggest that the strength can continue to develop past 28 days.